Learning Media of Ladder and Snake in Basic Dribbling Skills Basket Ball - Ruslan Rusmana; James Tangkudung; Firmansyah Dlis (STKIP Muhammadiyah Kuningan, 2019)
The The purpose of this study was to learn about the use of large media games in order to improve students' dribbling skills in basketball games. The number of participants was 30 people consisting of 18 female students and 12 students of SMK IT Nurul Imam, the research method used experiments with pre-test and post-test one design group. With training, the media provides snake ladder games in the learning process. The research process lasted for 5 weeks with the results of data analysis showing the average value obtained by students compilation of the students who did the pre-test at 22.33 and post-test at 26.56. It can be improved even though it's not too large with an average increase of 4.2. So it can be excluded from the use of the media ultimat significant importance to the results of basic basketball dribbling skills of students. Data analysis techniques used with pre-test and post-test with student instruments dribbled on zig zag tracks